Does de-capacity policy enhance the total factor productivity of China's coal companies? A Regression Discontinuity design. (October 2020) - Zhang, Weike; Meng, Jia; Tian, Xiaoli
Abstract: China's overcapacity in the coal industry has become increasingly prominent since 2013, with a severe negative impact on resource allocation and the national economy. The Chinese government has implemented a series of de-capacity policies to resolve overcapacity and improve the total factor productivity (TFP) in the coal industry. In this study, we aim to explore whether the de-capacity policy enhances the TFP growth of China's coal companies. We firstly apply the Super-SBM-Malmquist index method to measure the TFP and its decomposition items (e.g., technical change, efficiency change) of China's coal industry. We then construct the Regression Discontinuity (RD) design to examine the impact of de-capacity policy on the TFP growth of the coal companies. The main results are as follows: (1) After the implementation of the de-capacity policy in 2016, the average TFP growth and technical change of the coal companies have increased significantly. (2) The de-capacity policy can dramatically promote TFP growth and technical change of the coal companies. In contrast, it has a significant and negative effect on efficiency change. (3) The positive impact of de-capacity policy on technical change is more significant than its adverse effects on efficiency change, which is the main reason for the increase in TFP growth. Therefore, the government should give full play to the positive role of administrative means in resolving overcapacity, and promote sustainable technological innovation of the coal industry. Highlights: The TFP and its decomposition items are measured using Super-SBM-Malmquist index method. We examine the impact of de-capacity policy on the TFP of the coal companies using the Regression Discontinuity design. The de-capacity policy can dramatically promote TFP growth and the TECH of the coal companies. The positive impact of de-capacity policy on TECH is more significant than its adverse effects on EEFCH.